Crimes against the environment - Rebovich, Donald J.; Curtis, George E., 1942- (New York, NY : Routledge, 2021)
"Crimes against the Environment explains the seriousness of the threat posed by pollution, its roots, how it has evolved, how it differs across the planet, and how society has endeavored to create and enforce laws directed at its control. Rebovich and Curtis begin with an overview of hazardous waste, the industries that produce toxins, available methods of waste treatment, and the legal environment of environmental crime. They examine the forces driving criminal behavior and the methods offenders adopt, as well as protections against polluters and their effectiveness. The book concludes with an examination of environmental justice in the US and globally, and looks ahead to the future of crime control and prevention in this arena. Case studies and discussion questions offer further perspective on these challenging issues of environmental integrity. This text serves undergraduate or early-stage graduate students majoring in criminal justice, environmental science, sociology, and political science, and could also serve as a resource for professionals in environment-related occupations"--
OCLC-licensed vendor bibliographic record.
Keywords: Offenses against the environment; Pollution prevention; Hazardous waste management industry; Hazardous wastes -- Law and legislation; LAW / Criminal Law / General; LAW / Environmental; LAW / Forensic Science